Npas4 regulates medium spiny neuron physiology and gates cocaine-induced hyperlocomotion - Lissek, Thomas; Andrianarivelo, Andry; Saint-Jour, Estefani; Allichon, Marie-Charlotte; Bauersachs, Hanke; Nassar, Merie; Piette, Charlotte; Pruunsild, Priit; Tan, Yan-Wei; Forget, Benoit; Heck, Nicolas; Caboche, Jocelyne; et al. (EMBO reports, 2021)
We show here that the transcription factor Npas4 is an important regulator of medium spiny neuron spine density and electrophysiological parameters and that it determines the magnitude of cocaine-induced hyperlocomotion in mice. Npas4 is induced by synaptic stimuli that cause calcium influx, but not dopaminergic or PKA-stimulating input, in mouse medium spiny neurons and human iPSC-derived forebrain organoids. This induction is independent of ubiquitous kinase pathways such as PKA and MAPK cascades, and instead depends on calcineurin and nuclear calcium signalling. Npas4 controls a large regulon containing transcripts for synaptic molecules, such as NMDA receptors and VDCC subunits, and determines in vivo MSN spine density, firing rate, I/O gain function and paired-pulse facilitation. These functions at the molecular and cellular levels control the locomotor response to drugs of abuse, as Npas4 knockdown in the nucleus accumbens decreases hyperlocomotion in response to cocaine in male mice while leaving basal locomotor behaviour unchanged.
Gesehen am 17.12.2021